Monitoring Biofilm Formation and Microbial Interactions that May Occur During a Salmonella Contamination Incident across the Network of a Water Bottling Plant - Karampoula, Foteini (Microorganisms, 2019)
The present study aims to monitor the ability of Salmonella to colonize and compete as a member of the mixed species biofilm within key points at a water bottling plant, in case of a contamination incident with this major foodborne pathogen. To achieve this goal, bacterial communities throughout the production line were collected and their identities were investigated by microbial counts and polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE). These bacterial communities alone or along with constructed Salmonella enterica serovar Typhimurium (ST) fluorescence-based bioreporters were left to form a biofilm on stainless steel for 6 days at 20 °C. ST bioreporters were constructed by introducing plasmids expressing EYFP (enhanced yellow fluorescent protein) fusions of the genes csgB, csrA, sspH2, and fliD into ST 14028S. The bead vortexing-plate counting method was applied for the enumeration of the biofilm population, while the behavior of the bioreporters was evaluated by fluorescence microscopy. From a set of 16 samples that were collected from the plant, species of Citrobacter, Staphylococcus, Pseudomonas, Bacillus, and Exiguobacterium were identified. The presence of these indigenous bacteria neither inhibited nor enhanced the biofilm formation of ST in mixed bacterial communities (p > 0.05). Furthermore, the csrA-based bioreporter was shown to be induced in multispecies biofilms with Citrobacter. In conclusion, this study enhanced our knowledge of bacterial interactions occurring within a biofilm in a water bottling plant.